The leveling-off of oxygen uptake is related to blood lactate accumulation. Retrospective study of 94 elite rowers - Lacour, J.-R.; Messonnier, L.; Bourdin, M. (European Journal of Applied Physiology, 2007)
To assess whether the ability to demonstrate a plateau in oxygen consumption (\mathop V.O2)(VO2) could be related to adaptation to exercise, the data obtained over a period of 10 years on 94 elite oarsmen who had participated in annual testing were re-evaluated. The test consisted in an incremental step protocol until volitional exhaustion. \mathop V.O2,VO2 heart rate (HR), blood lactate ([La]b) and respiratory exchange ratio (RER) were measured at each step. The maximal oxygen consumption (\mathop V.O2max),(VO2max) the power corresponding to \mathop V.O2max(Pamax)VO2max(Pamax) and the maximal power achieved (Ppeak) were recorded. Thirty-eight oarsmen achieved a \mathop V.O2VO2 plateau and were designated as Pla; 56 did not and were designed as N-Pla. The Pla and N-Pla \mathop V.O2max, PamaxVO2maxPamax and maximal HR values were similar. In comparison with N-Pla, the Pla group displayed a rightward shift of the [La]b versus power curve, accounted for by both the increased percentage of \mathop V.O2maxVO2max corresponding to 4 mmol l-1 and the decreased value of [La]b corresponding to Pamax (P < 0.05). Pla oarsmen attained a higher Ppeak expressed as % of Pamax (P < 0.05) and also showed better ergometer performance (P < 0.05). In a sub-group of 53 oarsmen constituted on the basis of Pamax values close to 400 W, for a given power output, the Pla subjects had significantly lower HR, RER, and [La]b values at each sub-maximal stage of the test. These results suggest that achieving a \mathop V.O2VO2 plateau during completion of an incremental step protocol accounts for greater muscle ability to maintain homeostasis during exercise. These differences give the oarsmen an advantage in rowing competitions.